A Multi-Omics Pan-Cancer Analysis of 4EBP1 in Cancer Prognosis and Cancer-Associated Fibroblasts Infiltration - Du, Kunpeng; Zou, Jingwen; Liu, Chunshan; Khan, Muhammad; Xie, Tao; Huang, Xiaoting; Zhang, Ke; Yuan, Yawei; Wang, Baiyao (Frontiers in Genetics, 2022)
Abstract Background: Eukaryotic Translation Initiation Factor 4E Binding Protein 1 (4EBP1) involved in inhibition of protein translation and synthesis. However, the phosphoprotein of 4EBP1 (p-4EBP1) promotes the translation and synthesis of several proteins, including multiple classic oncogenic proteins. The prognostic significance of 4EBP1 mRNA, 4EBP1 protein, and p-4EBP1 in Pan-cancer are still unclear. Methods: In this study, we provided a multi-Omics investigation for the prognostic value of 4EBP1 mRNA, 4EBP1 protein, and different 4EBP1 phosphoproteins in a Pan-cancer manner based on the TCGA projects. We explored the correlation between 4EBP1 expression and the cancer-associated fibroblast (CAFs) infiltration, respectively using the EPIC, MCPCOUNTER, and TIDE algorithms. The functional states of 4EBP1 were explored using single-cell sequencing analysis in Pan-Cancer. Immunohistochemistry staining was used to detect and verify the expression of 4EBP1 in several cancers. Results: 4EBP1 mRNA was aberrantly overexpressed in most cancers, and was associated with the poor prognosis in ten cancers. Notably, increased 4EBP1 mRNA expression significantly correlated with tumor staging and worse prognosis in BRCA, KIRC, and KIRP, while having the opposite effect in STAD. 4EBP1 expression was associated with the CAFs infiltration level in ten cancer types. Interestingly, the correlation between 4EBP1 and CAFs infiltration had pronounced heterogeneity in digestive system tumors and urinary system tumors. In BLCA, KIRC, and ACC as well as BRCA, 4EBP1 was significantly positively correlated with CAFs infiltration and was associated with a poor prognosis. In STAD and COAD, 4EBP1 is negatively correlated with CAFs infiltration and was associated with a better prognosis. Lastly, the expression and prognostic significance of 4EBP1 protein and different p-4EBP1 varied enormously among cancers. Conclusion: Our multi-omics study indicates that 4EBP1-driven CAFs infiltration is associated with cancer prognosis and 4EBP1 mRNA, 4EBP1 protein, and p-4EBP1 proteins may serve as potential prognostic biomarkers and therapeutic targets in diverse cancer.